On the Australian linyphiid spider Alaxchelicera ordinaria Butler, 1932 (Araneae) - Scharff, Nikolaj; Hormiga, Gustavo (Zootaxa, 2013)
Very few studies have addressed the linyphiid fauna of Australia. Most of the existing taxonomic work on Australian linyphiids consists of isolated species descriptions (e.g., Rainbow 1912) or at most are based on small number of species also described outside a revisionary context (e.g., Wunderlich 1976) (but see van Helsdingen 1972 for a revision of the Australian species of the genera Laperousea Dalmas, 1917 and Laetesia Simon, 1908).